PENGARUH KOMUNIKASI TERHADAP MOTIVASI KERJA KARYAWAN PADA SMP NEGERI 03 BELITANG MADANG RAYA OKU TIMUR - Afrina, Iin; Hudawi, M Nuh; Zaidun, Zaidun (STMIK Pringsewu, 2024)
The problem faced by the SMPN 03 Belitang Madang Raya School East OKU is how the influence of communication on the work motivation of the employees at the SMPN 03 Belitang Madang Raya School East OKU is, while the purpose of this study is to determine the effect of communication on the work motivation of employees at the SMPN 03 Belitang Madang Raya School East OKU. The proposed hypothesis is that there is a strong influence between communication on employee work motivation at the SMPN 03 Belitang Madang Raya School East OKU. From the calculation results obtained the results of r = 0.604. After consulting with a conservative standard, it turns out that 0.604 lies between 0.600 - 0.799 which is included in the strong correlation. Then to answer the hypothesis test proposed in the previous chapter has a relationship or not, then it is tested by hypothesis testing and obtained t count = 2.143. While the value of t table at the 95% confidence level for (n – 2 ) = 1.860. Then it can be seen that the t-count value is 2.143 which is greater than the t-table value = 1.860, thus means (Ho) is accepted and (Ha) is rejected.